PERAN AYAH DALAM PENGASUHAN: TINJAUAN KISAH NABI IBRAHIM DAN NABI ISMAIL DALAM AL-QUR’AN - Aulia, Rahmadianti (Al-Qalb : Jurnal Psikologi Islam, 2017)
The aim of this research is to describing the important value of father contribution for children in parenting. This research observed Ibrahim and Ismail true story in al-Quran. Many researchers was proved that father in parenting has positives impact to development mentality of children. This research applied descriptive qualitative method in which the data are obtained from dialog verses in al-Quran. The data are collected by observational method supported by note-taking. After analyzing the data its show that al-Quran was earlier educating and applying this concept. What al-Quran said even today is still relevance with modern era. In the other words Islam has been applying father parenting system since the beginning and will always compatible for the future later.